2022
DOI: 10.1002/est2.354
|View full text |Cite
|
Sign up to set email alerts
|

An attention‐based synthetic battery data augmentation technique to overcome limited dataset challenges

Abstract: Large‐scale global efforts for electrifying different modes of transportation have fueled the need for energy‐dense storage systems. Lithium‐ion batteries have shown promise to be a favourable technology to power pure electric vehicles, off‐board storage systems for microgrids and other hybrid vehicle applications. Accurate estimation of vital battery parameters, such as state‐of‐charge, enable the user to predict remaining useful life of lithium‐ion batteries. Although multiple data‐driven techniques over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…A possible solution to overcome these problems is the usage of artificially augmented data. In the last few years, it has been shown that data augmentation techniques can lead to improved results for ML models, thus making it possible to successfully tackle the problem of limited datasets [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…A possible solution to overcome these problems is the usage of artificially augmented data. In the last few years, it has been shown that data augmentation techniques can lead to improved results for ML models, thus making it possible to successfully tackle the problem of limited datasets [29][30][31].…”
Section: Introductionmentioning
confidence: 99%